Inducción y tentativa : una aproximación desde el delito de inducción a la prostitución en colombia (2021)
In Judgement SP122-2018 Colombia's Supreme Court did an interpretation of article 213 of the Penal Code, which contains the crime of incitement to prostitution -inducción a la prostitución-. In that ruling the Court established that the crime of incitement to prostitution was consummated even when the victim is not convinced by the proposition. In other words, according to that judgement no result is necessary for the crime to be consummated. This paper comprises a critical analysis of the Supreme Courts judgement, emphasizing on the flaws that that particular interpretation has. Furthermore, starting from that analysis, the author proposes a different interpretation of the typical action -inducir-; one that actually respects the principles of criminal law and is coherent with the legal right -bien jurídico- that is being protected. Additionally, the paper poses other considerations regarding incitement to prostitution, such as: the compatibility between the figure of attempt and the crime of incitement to prostitution, and the possibility of committing this crime through the web.